117k views
2 votes
Hey there! it will be a big help if you lend a hand here! thank you <3

Hey there! it will be a big help if you lend a hand here! thank you <3-example-1
User Ciastek
by
5.4k points

2 Answers

7 votes

Answer:

54

Explanation:

since x= 0.6 and y=5 you replace them in 2(xy)^3

then it would be 2((0.6)(5))^3

first multiply the numbers inside 0.6 times 5 =3

second multiply 3 three times =27

lastly multiply 27 times 2 to get finally 54

hope this helped :)

User Andrea Sindico
by
5.1k points
7 votes

Explanation:

2(xy)^3

= 2(0.6 * 5)^3

= 2(3)^3

= 2 * 27

= 54

User Mway
by
5.3k points